Linoleic Acid Reduces Oxidative Phosphorylation and Impairs Early Differentiation of MC3T3-E1 Osteoblast Precursor Cells. (14th June 2022) - Nesbeth, Paula-Dene; Ziegler, Thomas; Weiss, Daiana; Hao, Li; Smith, Matthew; Jones, Dean; Weitzmann, M Neale; Alvarez, Jessica
Abstract: Objectives: Untargeted metabolomics analyses by our group have shown that plasma linoleic acid (LA) was inversely associated with bone mineral density Z-score and that bone formation indices were associated with energy-generating metabolic pathways, including fatty acid b-oxidation, in adult cohorts. Here, we examined the effect of increasing LA concentrations on osteoblast precursor cell bioenergetics and osteoblast differentiation to determine whether high LA is detrimental to bone formation. Methods: We treated MC3T3-E1 pre-osteoblastic cells with 0 µM (control), 1 μM, and 50 μM LA cultured in osteogenic differentiation media supplemented with 50 µM L-ascorbic acid and 2 mM β-glycerophosphate. To assess the effect of LA on early commitment/differentiation, cells were stained for alkaline phosphatase activity and late differentiation using Alizarin Red S staining for mineral deposition, at 7 and 18 days, respectively. To assess cellular bioenergetics, real-time ATP production rates in LA treated (1 or 50 μM) and control MC3T3-E1 cells were measured using an extracellular flux analyzer after 24 hours (normalized for total protein content). Differences in bioenergetic values were determined using one-way ANOVA or Kruskal-Wallis test with Tukey's HSD or Dunn's post hoc tests. Results: While LA had no effect on late differentiation/mineralizing activity of MC3T3 cells, LA dose-dependently decreased commitment/early differentiation. LA also significantly altered the bioenergetic profile of MC3T3-E1 cells by decreasing basal oxygen consumption rate (P < 0.001), as well as mitochondrial and total ATP production rate (P < 0.05 and P < 0.001, respectively). There were no significant changes in glycolytic ATP production rate. Conclusions: Osteoblast differentiation is a highly bioenergetic process, and this study suggests excess LA may impair ATP production from oxidative phosphorylation. This, in turn, may impede commitment and early differentiation of osteoblasts. Our study supports further clinical and translational investigation into the role of LA and energy metabolism in osteoblast function, as well as bone formation. Funding Sources: National Institutes of Health.